2003
DOI: 10.1177/1087057103258284
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Graphical Methods for Quality Control Determination of High-Throughput Screening Data

Abstract: High-throughput screening (HTS) is used in modern drug discovery to screen hundreds of thousands to millions of compounds on selected protein targets. It is an industrial-scale process relying on sophisticated automation and state-of-the-art detection technologies. Quality control (QC) is an integral part of the process and is used to ensure good quality data and minimize assay variability while maintaining assay sensitivity. The authors describe new QC methods and show numerous real examples from their biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 1 publication
0
53
0
Order By: Relevance
“…Results were normalized and corrected for systematic errors using the B score. 18 Compounds with a B score value lower than 3 times the SD were empirically considered hits in the assay.…”
Section: Identification Of Inhibitors Of Survivin Transactivationmentioning
confidence: 99%
“…Results were normalized and corrected for systematic errors using the B score. 18 Compounds with a B score value lower than 3 times the SD were empirically considered hits in the assay.…”
Section: Identification Of Inhibitors Of Survivin Transactivationmentioning
confidence: 99%
“…Studies have shown that Z factor is the most favorable among these classical metrics 16 B4: Adjusted data of a plate in 2nd screen…”
Section: Analytic Methodsmentioning
confidence: 99%
“…Position effects, especially edge effects, commonly exist in HTS assays. [15][16][17][18]22 Smoothing methods or robust regressions are usually adopted to adjust for systematic errors due to position effects. In this study, we used local polynomial regression fitting 36 of measured intensities on row and column numbers to adjust for the systematic errors related to positions in the ApoA1 experiments.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of systematic errors of measurement is not uncommon in HTS experiments. 13,[26][27][28] A good plate design helps to identify systematic errors (especially those linked with well position) and to determine what normalization we should use to adjust the data so that we can remove/reduce the impact of systematic errors on both QC and hit selection. Currently, the commonly used plate designs cannot effectively identify and adjust for systematic errors.…”
mentioning
confidence: 99%